New products Phoenix Suns - Fagan, Paul D.; Austen Press; RMI Media Productions (Olathe, KS : RMI Media Productions, 1995)
Shows how the Phoenix Suns brings NBA star player Charles Barkley, a new product feature, to its team and how they uses this marketing gem to promote new products.
Narrator: Tom Leander.
Keywords: Marketing -- Case studies; New products -- Marketing -- Case studies; Product management